Surveying the changing climate of Northern Territory medical workforce retention. (1st March 2022) - Pendrey, Catherine; Quilty, Simon; Lucas, Robyn
Abstract: Introduction: Low retention is a significant contributor to medical workforce shortages in rural and remote regions of Australia, including in the Northern Territory (NT). Many of these areas are susceptible to climate change, which could exacerbate workforce retention problems. Objective: To examine factors influencing medical workforce retention in the NT, including the potential impact of climate change. Design: Cross sectional online survey of NT medical professionals, distributed via email through professional networks. Predominantly quantitative mixed methods (descriptive statistics, multivariate logistic regression, thematic analysis). Main 2 outcome measures reported were proportion of respondents intending to leave the NT, timeframe of intention to leave and motivating factors. Findings: Of 1407 registered practising medical professionals in the NT, 362 responded who met inclusion criteria (26% estimated response rate) and 351 completed all questions. Of the latter, 143 (41%) intended to leave the NT, 102 (29%) were unsure, and 106 (30%) did not intend to leave. Among doctors in training (DITs) 67 (55%) intended to leave and 29 (24%) were unsure. The best multivariable predictive model included only practice type (with general practitioners/rural generalists and non‐GP specialists significantly less likely to intend to leave compared to DITs), and location of primary medical degree (with non‐NT training non‐significantly associated with greater intention to leave). Of those intending to leave 94 (66%) reported planning to do so within two years. Training and career development opportunities, job dissatisfaction, moving to a preferred location and family‐related factors were all important motivators. Of those considering leaving, 58 (24%) identified climate change as a motivating factor. Conclusion: Retention remains a key challenge in addressing rural workforce shortages. In addition to established factors, climate change is an important driver that has the potential to worsen workforce shortages in susceptible regions.